PERLINDUNGAN HUKUM BAGI PARA PIHAK YANG DIRUGIKAN DALAM BIDANG PERTANAHAN AKIBAT PERISTIWA BENCANA ALAM TERKAIT BERGESERNYA BATAS TANAH - Amirsyah Amirsyah; Felicitas Sri Marniati; Basuki Basuki (Jurnal Ilmiah Global Education, 2023)
Land in Indonesia still remains but its use is increasing and makes the value of land prices also go up, so it often causes conflict. Therefore, a complete settlement is needed that can be accepted by the litigants so that justice is created between the litigants. In this study raised two problems, namely how the legal consequences of natural disaster events that resulted in a shift in land boundaries and how the legal protection for the injured parties related to the shifting of land boundaries?. The method used is a normative juridical research method that initiates the collection of legal materials carried out by identifying and inventory of positive legal rules, researching library materials (books, scientific journals, research reports), and other sources of legal materials relevant to the legal issues under study. The results of this study suggested that the land shifted boundaries that can not be proved again because of the physical data is lost, so it is no longer in accordance with the physical data and juridical data as a strong evidence, it can solve the problem with physical evidence and non-physical in court and outside the court as UUPA and PP No. 24 of 2007 on Land Registration. However, in Article 43 of the regulation of the Minister of Agrarian Affairs and Spatial Planning / head of the National Land Agency of the Republic of Indonesia number 21 of 2020 concerning the handling and settlement of land cases is a form of legal protection against the community regarding dispute resolution that can be resolved through mediation at the initiative of the ministry, Regional Office, Land Office and so on.